General Design Layout of Datengxia Ship Lock - LI Yawen; CHEN Guihua (Renmin Zhujiang)
The Datengxia hydro project is a key project to open the 100-million-ton golden waterway of the Xijiang River,with high navigation requirements for the dam-site reach and a huge freight volume.The general design layout of the navigation structure ship lock plays a vital role in the layout scheme,freight volume,operation management,and investment of the whole hydro project.For the general design of the ship lock, the position of the ship lock is first selected according to the topographical and geological conditions of the project area and the layout requirements of the hydro project.On this basis,this study designs the lock head,lock chamber,water conveyance system,upstream and downstream approach channels,entrance area and connecting section,anchorage to be locked,etc.Additionally,the structural dimensions of the water conveyance system and rectification measures in the entrance area are optimized according to the model test results.The Datengxia ship lock has reached the highest level of ship locks built at home and abroad in terms of the scale,water head,water-level variation amplitude conditions,and hydraulic index requirements.Its general layout can provide a certain reference for the design of large-scale and high water-head ship locks.